Artificial Intelligence Utilization, Digital Literacy, and Employee Productivity in Indonesian Organizations - Kapsah (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
Digital transformation has encouraged organizations to adopt Artificial Intelligence (AI) as a strategic technology to improve operational effectiveness and organizational competitiveness. However, the successful implementation of AI depends not only on technological sophistication but also on employees' ability to utilize the technology effectively through digital literacy. This study aims to examine the effect of Artificial Intelligence utilization on employee productivity, with digital literacy serving as a mediating variable in Indonesian organizations. This study employed a quantitative approach using an explanatory research design. Data were collected through a questionnaire survey involving 200 employees working in organizations that have implemented AI in their operational activities. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with SmartPLS 4 software. The findings indicate that AI utilization has a positive and significant effect on both employee productivity and digital literacy. Furthermore, digital literacy positively influences employee productivity and significantly mediates the relationship between AI utilization and employee productivity. These findings demonstrate that improving employee productivity depends not only on technology adoption but also on strengthening employees' digital competencies. This study contributes to the development of the Resource-Based View perspective by explaining the synergy between technological capabilities and human capabilities, while providing practical implications for organizations in designing sustainable digital transformation strategies.